Letter from Carl Duncan to Patricia Whiting, November 15, 1966 - Duncan, Carl D. (Carl Dudley), 1895-1966:::Creator::::::::::::
Duncan mentions recovering from a recent illness and suggests plans for dinner with Whiting.